Expression of epidermal growth factor receptor in breast carcinoma. Issue 5 (May 1990) - Lewis, S; Locker, A; Todd, J H; Bell, J A; Nicholson, R; Elston, C W; Blamey, R W; Ellis, I O
Abstract : A series of 90 patients with primary operable breast cancer and with up to 36 months of follow up were investigated for expression of epidermal growth factor receptor (EGFR) in their tumours by immunocytochemical staining with the monoclonal antibody EGFR 1. Tumour samples were snap frozen in liquid nitrogen immediately after resection and subsequently stained using a standard indirect immunocytochemical method. Tumour staining was assessed by two observers and scored on a four point scale (0-3). Thirteen (14%) tumours showed positive immunoreactivity. A strong correlation between distinct EGFR expression and short disease free interval was observed. Significant correlations were also shown with oestrogen and progesterone receptor expression and tumour nuclear size. No significant association was found with tumour size, lymph node stage, and histological grade. The association with disease free interval remained significant in multivariate analysis.